Liverpool of the Cape: Port Elizabeth harbour development 1820-70 - Inggs, Eric Jonathan (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 1987)
Fairy tales aside this study is an analysis of Port Elizabeth harbour development during its first half century from 1820-70. Despite the fact that Port Elizabeth quickly came to dominate Cape trade very little was actually done to improve its port facilities. Superficially the impression one gains from the available material is that everything was done by government not to develop a harbour at Algoa Bay. But the real question is: was harbour development really necessary at Port Elizabeth during the period under consideration? The answer must be no. The lack of facilities certainly did not hinder the massive expansion of wool exports that took place before 1870.
Keywords: Harbors -- South Africa Port Elizabeth; Exports -- South Africa Port Elizabeth; Imports -- South Africa Port Elizabeth; Eastern Cape (South Africa) History